Numerical study on effect of relative humidity (and fuel moisture) on modes of grassfire propagation. (October 2021) - Moinuddin, Khalid; Khan, Nazmul; Sutherland, Duncan
Abstract: Relative humidity of air is directly related to fuel moisture. Fuel moisture is often considered as the index of flammability in the context of bushfire. Variation of relative humidity and fuel moisture is considered to have a significant effect on the rate of spread of grassfire propagation and fire intensity. In this study, four sets of grassfire simulations have been conducted: three sets with 210 mm high grass and another set with 175 mm high grass. For all sets, the ambient temperature was kept constant while relative humidity and fuel moisture were varied, with fuel moisture deduced from the McArthur MKV GFDI model. With 210 mm grass heights, driving wind velocities were varied. Lower relative humidity (and fuel moisture) was observed to lead to higher fire intensity and a faster rate of spread, which are intuitively expected. Byram number analysis showed that relative humidity (and fuel moisture) can lead to change in the fire propagation mode (wind-driven vs buoyancy-driven), but the greater factor is the wind velocity.